SOCIOLOGIA DO TRABALHO DOCENTE: Formação e condições de trabalho de professores de Sociologia nas escolas públicas estaduais do ensino médio no Maranhão - GARCIA, Andréa Joana Sodré de Sousa (2024)
The aim of this study was to understand the training process, starting with the institutionalization of Social Sciences courses in Maranhão, as well as the curricular structures that led to the training of the first high school sociology teachers. In addition to this process, we also sought to identify the sociographic profile and working conditions of sociology teachers in state schools in Maranhão. With the enactment of Law No. 11.684 of 2008, which made sociology compulsory in all three grades of high school, the states and the federal government, through their secretariats, ministries and higher education institutions, began a series of processes with the aim of training more professionals with a degree in sociology, in order to meet the demands of the school networks (public and private). Here in Maranhão, in addition to the Social Sciences courses offered by the public universities: Federal (1986) and State (2006), both in the capital São Luís, other programs and courses have been created: Ensinar Program/UEMA ; National Basic Education Teacher Training Program - PARFOR; Degree in Social Sciences UEMA/Caxias; Teacher Training Program for Ethnic Diversity - PROETNOS/UEMA with the aim of making up for the shortage of teachers in the interior of the state. Over the last 10 years, the literature in this area has focused on the history of the subject, methodological teaching strategies and training modalities, etc. However, there are few studies that seek to investigate training and professional insertion into the job market and the objective conditions of teaching work, especially in Maranhão, where this study is still non-existent. We therefore carried out a survey and analysis of the training courses and their curricular structures, with the aim of understanding how sociology teachers who teach in Maranhão's secondary schools are trained. We also conducted interviews with teachers from this network, making it possible to draw up a profile of these teachers and analyze their working conditions at school before and after the implementation of the New Secondary Education (Law No. 13,415/2017). Thus, we hope to contribute to the production on the teaching of Sociology in Basic Education. The method used during the research was of a documentary, qualitative and quantitative nature, applying questionnaires and semi-structured interviews. The research revealed that after the introduction of the comprehensive school and the implementation of the New High School, there was an increase in the precariousness of the work of sociology teachers in high school generated, among other factors, by the reduction in their workload, redirecting this teacher to diversified disciplines, such as: life project, coresponsibility, tutoring, formative pre-itineraries, etc., in which they have neither training nor material for study. This process is the result of the deliberations of neoliberalism, which is boycotting advances in public education, as we will see in the course of this work.